Budaya organisasi dan kode etik pustakawan dalam implementasinya - Panti Panti (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2015)
Librarians actually played a major role in contributing to the development of a civilized. but its role is not seen by most people . The problem is when people seeing  the library, as if the librarian is blocked by a row of collection that is increasingly to be older  and increasingly away from the elements to present . That said, when mentioning the word library, people thinks refer to a medium of human civilization, namely books. For a long time, the book became the primary knowledge resource, compiled by the library. This happens because the position of the library was considered only as a storage place only, and turns up the assumption that the modern age so shall still can not be eliminated. Judging by the cases me "minor" the role of librarians as noted above, provide opportunities for us to further tracing the pattern of the existing organizational culture Keywords: Librarian, Organizational culture